Adjuvant effects of chemotherapeutics and metformin on MFE-319 endometrial carcinoma cell line - Aydemir, Işıl; Türköz Uluer, Elgin; Korkmaz, Oya; Tu?lu, Mehmet İbrahim; İnan, Sevinç (Editura Academiei Romane, 2020)
We aimed to investigate the cytotoxicity of Metformin, Cisplatin, and Paclitaxel on MFE-319 endometrial carcinoma cell line using 3-(4,5- dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and immunocytochemistry assays. Half maximal inhibitory concentration (IC50) doses of three drugs alone and in the dual combinations were applied to the cells. Immunocytochemical method was performed for the cell survival and for phosphatidylinositol 3-kinase (PI3K), phosphorylated extracellular regulated kinases (pErk)-1/2, Akt-1, phosphorylated Akt (pAkt)-1/2/3 cell growth markers and angiogenic vascular endothelial growth factor (VEGF). Immunoreactivities were evaluated using H-score and analyzed using the one-way analysis of variance (ANOVA) test for statistics. It was found that these drugs caused a decrease in the immunoreactivities of these markers. Particularly, dual combination of Paclitaxel and Cisplatin decreased the immunoreactivities of PI3K, pErk-1/2, Akt-1, and pAkt-1/2/3. Cisplatin and Paclitaxel were more effective than Metformin; on the other hand, Metformin has been shown to enhance the efficacy of these two drugs. In vitro or in vivo further studies are needed to investigate the efficacy of these three drugs via PI3K/Akt signal pathway.
Keywords: Cisplatin; Endometrial Carcinoma; Metformin; PI3K/Akt; Paclitaxe